Pengaruh RGEC (Risk Profile, Good Corporate Governance Earning, Capital) terhadap Financel Distress - Fikri Hakim Ermar; Suhono Suhono (Politeknik Ganesha Medan, 2021)
This study aims to determine the effect of RGEC (Risk Profile, Good Corporate Governance, Earnings and Capital) on Financial Distress in banks listed on The Indonesia Stock Exchange (IDX) for the period of 2016-2019. The sample data used is the result of the purposive sampling technique and the samples declared worthy to be utilized are 21 banks. During the study conducted, the method was adopted which is a method of logistic regression analysis using SPSS 25 program aid. The results of the research show that the variables that are known can affect the Financial Distress is Return On Asset affect negatively and significantly. Meanwhile, variables that do not affect Financial Distress are Non-Performing Loan (NPL), Loan to Deposit Ratio, Good Corporate Governance, and Capital Adequacy Ratio. Simultaneously Non Performing Loans, Loan to Deposit Ratio, Good Corporate Governance, Return on Assets and Capital Adequacy Ratio have a significant effect on Financial Distress.